Formalism versus realism: the International Court of Justice and the critical date for assessing jurisdiction - Daniel West (UCL Journal of Law and Jurisprudence, 2016)
The 2011 judgment in Georgia v Russian Federation represents an apparent watershed in the approach of the International Court of Justice to ascertaining the critical date for assessing jurisdiction. With few historic exceptions, the Court had previously applied a doctrine of realism that allowed for the resolution of procedural defects between the date of seisin and the Court’s decision on jurisdiction. In Georgia, however, the Court applied a formalistic approach that assessed competence solely by reference to the date on which the application was filed, and accordingly declined jurisdiction. This vacillating approach to the critical date is an example of how the Court exercises interpretative discretion to further its own procedural objectives through engagement in judicial case selection. This practice will be criticised on two grounds: first for depriving the Court of opportunities to fulfil its primary function of developing international law, and second for betraying an institution that has applied formalism on an ad-hoc basis on political grounds. It will be concluded that the Court’s broader institutional function would be better served through the adoption of a blanket and permanent approach of flexible realism in allowing for the post-filing resolution of jurisdictional defects. NB: full text available at: http://discovery.ucl.ac.uk/1493218/
Keywords: Jurisdiction; International Court of Justice; International Law